(untitled) - Tiratira, Niclie L. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Using the working text in psychological evaluation through the two-group control group design, the study determines the student performance difference. It is hypothesized that pretest and post-test distributions are the same across group categories. Sixty (60) third-year students of BS Psychology who took the course in Psychological Assessment were the participants. Non-parametric tests of independent samples were used in the research. The Mann-Whitney U test, when the dependent variable is either ordinal or continuous, but not normally distributed, is used to compare differences between two independent groups. The data result showed that it is effective for the Worktext in Psychological Evaluation to have a substantial difference in the test group and control group post-test outcome.